Efficiency of application of watersoluble fertilizers in various doses when growing table watermelon under the conditions of the Volgograd region - T. G. Koleboshina; N. B. Ryabchikova (Овощи России)
Relevance. The article presents the results of studies to determine the effectiveness of the use of new types of water-soluble fertilizers in different doses. The obtained results will be used for the development of new agricultural practices and improvement of technologies for growing table watermelon. Materials and methods. The studies were carried out in the Volgograd Trans-Volga region at the Bykovskaya melon selection experimental station in 2018-2019. We studied the dose of water-soluble fertilizer on the quality of the watermelon table variety Triumph. Results. Studies have found that the use of water-soluble fertilizers has a positive effect on the yield and its structure. The advantage of using water-soluble fertilizer Hakafos with the content of nutrients in equal proportions dose of 900 g/100 l, yield 7.2-10.6% more compared to other studied water-soluble fertilizers with a similar dose and 44.7% more compared to pure control (without treatments). Evaluation of the results showed a positive effect of water-soluble fertilizers on the marketable qualities of watermelon fruits. In variants with the use of water-soluble fertilizers, the fruits are larger, 18.1-34.1% more compared to the control (without treatments), and 4.2-9.2% more yield of standard products. Studies have found that the use of water-soluble fertilizers do not have a negative impact on the quality and environmental purity of products, the amount of nitrates in the fruit does not exceed the maximum permissible values. The use of this agricultural technique in the technology of cultivation of table watermelon, as studies have shown, can significantly improve the economic performance of the production of this product.